Understanding right and wrong - Rosen, Michael, 1946-; Young, Annemarie (Social justice handbook., 2020)
Investigates the ideas behind people's senses of right and wrong, how one's upbringing and environment can shape and flaw one's sense of right and wrong, and how readers can develop a personal value system to guide them through life. Includes a glossary.